Screening characteristics for enrichment of individuals at higher risk for transitioning to classified SLE. (April 2019) - Young, K A; Munroe, M E; Guthridge, J M; Kamen, D L; Gilkensen, G S; Harley, J B; Weisman, M H; Karp, D R; Wallace, D J; James, J A; Norris, J M
Objective: Further prospective study is needed to elucidate the etiology and natural history of systemic lupus erythematosus development. The clinical complexity of this heterogeneous disease makes study design challenging. Our objective was to ascertain useful screening factors for identifying at-risk individuals for follow-up rheumatologic assessment or inclusion in prospective studies. Methods: We attempted to re-contact 3823 subjects with a family history of systemic lupus erythematosus, who did not meet American College of Rheumatology systemic lupus erythematosus classification at a baseline study visit; 436 agreed to follow-up participation an average of 6.3 years after baseline. In total, 56 of these individuals had transitioned to classified systemic lupus erythematosus (≥ 4 cumulative American College of Rheumatology criteria, verified by medical record review) by the time of follow up. Generalized estimating equations assessed associations between our dichotomous outcome of transitioning to systemic lupus erythematosus with baseline characteristics, including ANA positivity, Connective Tissue Disease Screening questionnaire systemic lupus erythematosus score, and number of American College of Rheumatology criteria. We analyzed predictive accuracy of characteristics on transitioning. Results: ANA positivity, Connective Tissue Disease Screening questionnaire systemic lupus erythematosus score categorization of possible or probable systemic lupus erythematosus, and greater number of American College of Rheumatology criteria at baseline were each associated with transitioning to systemic lupus erythematosus classification. Being ANA positive and having confirmed immunologic criteria at baseline had the highest positive predictive value and specificity for transitioning to systemic lupus erythematosus. American College of Rheumatology Connective Tissue Disease Screening questionnaire systemic lupus erythematosus score categorization of possible or probable systemic lupus erythematosus had a better positive predictive value, negative predictive value, sensitivity, and specificity than ANA positivity. Conclusion: Given limited resources, identifying individuals for follow up based on the systemic lupus erythematosus portion of the Connective Tissue Disease Screening questionnaire could be an efficient way to identify family members at highest risk of disease transition.